Multi-stimuli responsive supramolecular hydrogels based on Fe3+ and diblock copolymer micelle complexation. Issue 7 (14th January 2016) - Tao, Zhen; Peng, Kang; Fan, Yujiao; Liu, Yunfei; Yang, Haiyang
Abstract : We report a multi-stimuli responsive supramolecular hydrogel with great potential for biomedical application, which was composed of the micelle-forming diblock copolymer and physically cross-linked by complexation between ferric ions and carboxylic acid groups, exhibiting gel–sol transition caused by UV irradiation, multidentate ligands (EDTA) and redox agents (Na2 S2 O4 ). Abstract : Stimuli-triggered degradable hydrogels have found broad applications in controlled release of drugs, fragrances, flavourings and fertilizers. Recently, multi-stimuli responsive micelle-based hydrogels have gained focus, since they could respond to a combination of external stimuli. Herein, a multi-stimuli responsive supramolecular hydrogel with great potential for biomedical application was prepared, which was composed of the micelle-forming diblock copolymer poly[( N -isopropylacrylamide- co -2-nitrobenzyl acrylate)- block -( N, N -dimethylacrylamide- co -acrylic acid)] (P(NIPAM- co -NBA)- b -P(DMA- co -AA)), and physically cross-linked by supramolecular complexation between AA groups and ferric ions (Fe 3+ ), exhibiting gel–sol transition caused by UV irradiation, multidentate ligands (EDTA) and redox agents (Na2 S2 O4 ).